2002
DOI: 10.1007/s00417-002-0548-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation end products quench nitric oxide in vitro

Abstract: These data demonstrate that AGEs formed from the nonenzymatic glycation of proteins with reducing sugars quench NO activities in vitro. The results implicate AGEs as important modulators of NO activity and may be relevant to the impairment of endothelial functions observed in diabetes and aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
(51 reference statements)
1
7
0
Order By: Relevance
“…AGEs-related decrease of eNOS mRNA expression associated with low NOS activity and NO avaibility, by quenching NO [39], reduces endothelial cells' antiplatelet activity and increases expression of adhesion molecules [40], as well as PMN-endothelial cell adhesion [41]. This fits well with the recent data, which have shown that AGEs enhance the expression of endothelial cell adhesion molecules [10,11].…”
Section: Discussionsupporting
confidence: 87%
“…AGEs-related decrease of eNOS mRNA expression associated with low NOS activity and NO avaibility, by quenching NO [39], reduces endothelial cells' antiplatelet activity and increases expression of adhesion molecules [40], as well as PMN-endothelial cell adhesion [41]. This fits well with the recent data, which have shown that AGEs enhance the expression of endothelial cell adhesion molecules [10,11].…”
Section: Discussionsupporting
confidence: 87%
“…AGE cross-linking in vessel wall collagen increases the area of the extracellular matrix, resulting in increased stiffness of the vessel wall. AGEs have also been shown to interact with NO, reducing its bioavailability and activity (22), and to increase the adhesion of macromolecules, such as macrophages and LDL, to the vessel wall (23), and the adhesion of leukocytes to coronary fibroblasts (24). AGEs have been observed in atherosclerotic plaques, foam cells, and fatty streaks (25).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the AGE‐RAGE system is theoretically able to account for most of the observed spectrum of changes in nitrergic neurones in diabetes. The interaction between NO and AGEs may be even more complex: AGEs can also quench NO; 42 in turn NO can reduce the formation of AGEs 43 . The formation of AGEs in diabetes can therefore lead to suppression of NO in many ways; this in turn can further enhance AGE production, amplifying the original insult.…”
Section: Discussionmentioning
confidence: 99%